(untitled) (Ameghiniana, 2013)
The subgenus Gryphaea (Mimetostreon) Bonarelli in Bonarelli and Nágera (1921) is considered to be a junior subjective synonym of Maccoyella Etheridge (1892). Maccoyella bonarellii (Leanza, 1963) is redescribed, and shown to be similar to Maccoyella incuruata Waterhouse 1959 from New Zealand (Aptian? or Albian?) and M. rockwoodensis (Etheridge) from Australia (Albian). The age of the Patagonian species is probably Aptian. This genus is important paleogeographically. By restoring the three regions with Maccoyella to their probable lower Cretaceous positions, based on paleomagnetic, faunal and structural analyses, it is shown that Maccoyetla inhabited a restricted paleolatitudinal belt, close to 50° S to 60° S. It is now found over a much wider spread of latitudes, ranging from nearly 10° S to 50" S.